A Retrospective Study On Liver Function Tests & Urine Protein in Presumptive Non-Alcoholic Fatty Liver Cases Performed in A Local Private Laboratory Service - Saiful Bahri, Talip; Muhammad Hamdi, Mahmood; Azam Hafizi, Azmi Murad; Charisma Demai, Edmand; Vimal, Gengatharan; Kar Kiat, Ho (UNIMAS Publisher, 2022)
Non-alcoholic fatty liver disease (NAFLD) could be diagnosed either by imaging or histology, and laboratory parameters from Renal Function Test (RFT) such as Aspartate-aminotransferase (AST), Alanine-aminotransferase (ALT), Gamma-glutamyltransferase (GGT), as well as Urine Protein (UP). In this study, data were collected from Advanced Pathology Sdn. Bhd. The data was collected from random population in the year of 2020 were used to identify the association between the parameters of AST, ALT, GGT and UP in presumed NAFLD patients, which are being compared by age, and gender. The results show that the level of GGT shows an insignificant association between genders (p >0.05), but shows a statistically significant association between the age group of respondents (p <0.05). In addition, results from AST indicated that the gender of respondents has a significant relationship with AST (p <0.05), but an insignificant correlation between the age groups (p >0.05). The results also showed also that ALT had an insignificant correlation between the gender of respondents (p >0.05), but is significantly correlated with the age of respondents (p <0.05). Lastly, Chi-square test of independence gave a result of p-value = 0.137 (p >0.05), which proved insignificant correlation between the gender of respondents and presence of UP, and p-value = 0.261 (p >0.05), which proved insignificant correlation between age of respondents and presence of UP.